2007
DOI: 10.1186/1476-511x-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lyso-phosphatidylcholine concentration is decreased in cancer patients with weight loss and activated inflammatory status

Abstract: Background: It has been observed that ras-transformed cell lines in culture have a higher phosphatidylcholine (PC) biosynthesis rate as well as higher PC-degradation rate (increased PCturnover) than normal cells. In correspondence to these findings, the concentrations of the PCdegradation product lyso-phosphatidylcholine (LPC) in cancer patients were found to be decreased. Our objective was the systematic investigation of the relationship between LPC and inflammatory and nutritional parameters in cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 22 publications
12
94
1
Order By: Relevance
“…This has also been observed in other tumor cells (Jantscheff et al, unpublished data) and this effect can be discussed as one possible cause for the strongly reduced LysoPC plasma amounts observed in patients with advanced metastatic cancer (17)(18)(19)(20)(21). In addition, a radical shift in tumor cell membrane FA composition toward saturated FAs was observed, culminating between 48 and 72 hours without increasing after further LysoPC exposure (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This has also been observed in other tumor cells (Jantscheff et al, unpublished data) and this effect can be discussed as one possible cause for the strongly reduced LysoPC plasma amounts observed in patients with advanced metastatic cancer (17)(18)(19)(20)(21). In addition, a radical shift in tumor cell membrane FA composition toward saturated FAs was observed, culminating between 48 and 72 hours without increasing after further LysoPC exposure (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The FA composition of plasma LysoPC in healthy individuals is comparable with that of total plasma PL; our unpublished studies confirm that more than 31% of the plasma LysoPC molecules carry unsaturated FAs. Various clinical observations have shown that plasma LysoPC levels are often decreased in advanced metastatic cancer patients (17)(18)(19)(20), especially when weight loss and inflammatory processes occur (21). This finding suggests a deregulation of the aforementioned LysoPC balance by malignant tumors and clearly indicates the potential importance of LysoPC in metastatic and cachectic processes.…”
Section: Introductionmentioning
confidence: 60%
“…For example, relatively low (nanomolar) concentrations of lyso-PC recruit monocytes and induce pro-infl ammatory cytokine production in vitro ( 81 ). However, the concentration of lyso-PC in blood plasma of healthy persons usually ranges from 200 to 400 M ( 82,83 ), and similar levels have been reported in atherosclerotic tissues ( 45 ). Because lyso-PC, unlike PC, is membrane lytic, it is predominantly confi ned to lipoproteins or plasma proteins, such as albumin or immunoglobulins ( 83,84 ).…”
Section: Lp-pla 2 Expression In Apparently Healthy Subjectsmentioning
confidence: 99%
“…However, the concentration of lyso-PC in blood plasma of healthy persons usually ranges from 200 to 400 M ( 82,83 ), and similar levels have been reported in atherosclerotic tissues ( 45 ). Because lyso-PC, unlike PC, is membrane lytic, it is predominantly confi ned to lipoproteins or plasma proteins, such as albumin or immunoglobulins ( 83,84 ). As a result, only a fraction of lyso-PC is functionally active, and it is unclear how total concentration relates to bioavailability ( 73,85 ).…”
Section: Lp-pla 2 Expression In Apparently Healthy Subjectsmentioning
confidence: 99%
“…Further supporting this notion, plasma levels of LPC are correlated inversely with inflammatory parameters, such as plasma C-reactive protein and whole blood hydrogen peroxide levels in cancer patients (Taylor et al, 2007).…”
Section: Lpc/pc Ratiomentioning
confidence: 56%